Attitude and perception of English language program students towards oral presentation in improving their English-speaking skills - Banafi, Norah (Edelweiss Applied Science and Technology, 2025)
Oral presentation enhances English fluency and serves as a critical skill for university students and their future careers. This study explores attitudes and perceptions of oral presentation in improving English language speaking skills among final-year undergraduate English Language Program (ELP) students in Saudi Arabia. An exploratory study design was adopted, targeting all final-year undergraduate ELP students at King Khalid University’s (KKU) Muhayil female campus (n=130). A self-structured online questionnaire was distributed via Google Forms, with 119 students responding. Most ELP students reported no fear of oral presentations (73.9%) and could present efficiently (79.8%), though 71.4% experienced difficulties. The majority (87.4%) recognized oral presentations as beneficial for future careers. Over 88% perceived improvements in vocabulary and pronunciation through presentations. Faculty feedback was valued by 74.8% of students. Significantly, 89.1% believed oral presentations improved their English-speaking skills, while 83.2% reported increased confidence in speaking English fluently. KKU ELP students demonstrated positive attitudes toward oral presentations for developing English speaking skills. Saudi universities should continue oral presentation training to enhance students' English proficiency, which is essential for effective communication and career advancement.